S-shaped reverse sural flap for reconstruction of tissue defect on heel - Fathi, Hamid Reza (Burns Trauma, 2013)
Traumatic limb injury is a prevalent lesion in Iran. Motorcycle accidents are responsible for most of these traumatic lesions. Despite various reported techniques, the coverage of the Achilles tendon, malleoli, ankle and heel is still daunting and demanding procedure. S-shaped reverse sural flap is a modified technique of reconstruction. In this report of 6 patients underwent surgical reconstruction by this modified technique we discuss about the technique as a simple and safe technique with low morbidity rate and recommend using this technique in complex injuries.